2007
DOI: 10.1111/j.1365-294x.2007.03520.x
|View full text |Cite
|
Sign up to set email alerts
|

The origins of weedy rice

Abstract: Where do weeds come from? How do they evolve from nonweedy ancestors? In this issue of Molecular Ecology, Londo and Schaal examine the origin of weedy rice (Oryza sativa) populations in the USA. Analysing nuclear DNA sequence and microsatellite data, they show the importance of parallel evolution, hybridization, gene flow, and migration in the evolution of these weeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
(14 reference statements)
1
14
0
Order By: Relevance
“…). Agricultural habitats are known to favour expression of certain traits (Baker ), including rapid growth (Kane and Baack , but see Bommarco et al ), and genetic differentiation has been observed in other weeds moving between non‐agricultural and agricultural habitats (Kane and Rieseberg ).…”
Section: Discussionmentioning
confidence: 99%
“…). Agricultural habitats are known to favour expression of certain traits (Baker ), including rapid growth (Kane and Baack , but see Bommarco et al ), and genetic differentiation has been observed in other weeds moving between non‐agricultural and agricultural habitats (Kane and Rieseberg ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed that four different evolutionary pathways result in what we call weedy rice sensu lato (e.g. Kane and Baack ; Londo and Schaal ; Xia et al. ; Song et al.…”
Section: Weedy Rice: Origin Genetic Diversity and Adaptive Evolutionmentioning
confidence: 99%
“…Indeed, studies have shown that weedy rice populations across the world possess abundant phenotypic and genetic diversity (Cao et al. ; Kane and Baack ; Londo and Schaal ; Xia et al. ,b; Zhang et al.…”
Section: Weedy Rice: Origin Genetic Diversity and Adaptive Evolutionmentioning
confidence: 99%
“…Weedy rice infestations are responsible for significant yield losses, which are particularly severe in short varieties and late planting cultivation (Fogliatto et al [2010]). Weedy rice is so productive that it can spread and cause major economic damage (Kane and Baack [2007]), but it is impossible to control weedy rice during the rice cultivation period by herbicide because it belongs to the same species as the cultivated rice (Delouche et al [2007]; Suh [2003]).…”
Section: Introductionmentioning
confidence: 99%